Damage To Brick-Walled Buildings And Effective Ways To Strengthen Brick Structures When Baratarafing Them - Mirzaakhmedov Abdukhalim Takhirovich (Zien Journals, 2024)
This article examines the causes of defects in brick walls, research into the actual operation of structural elements, and improvement of methods for the reliable elimination of cracks, deformations, damage and distortions that arise when assessing their technical condition
Keywords: brick walls; complete set of walls with bricks; load-bearing and enclosing structures